ALGEBRAIC AND GEOMETRIC METHODS IN MATHEMATICS - Fazlidin Batirovich Kurbanov (Uzbekistan Open Conference, 2025)
We will examine the concepts of “algebraic method” and “geometric method” as methods in the science of mathematics. Algebraic and geometric methods in mathematics are approaches to problem solving based on different approaches: algebraic (working with formulas and variables) and geometric (using visual objects and drawings). These methods are interrelated, as sometimes a problem requires both.
Keywords: Algebra; geometry; mathematics; arithmetic; methods; technology; equations; problem; solutions